2018
DOI: 10.11118/actaun201866020487
|View full text |Cite
|
Sign up to set email alerts
|

Formulation for Development Strategy of Gayo Coffee Agroindustry Institution Using Interpretive Structural Modeling (ISM)

Abstract: Institutional aspect is one of strategic aspect for an agroindustry development, including Gayo coffee agroindustry in Province of Aceh, Indonesia. Institution has important role as medium for innovation distribution, certification, and quality management of agroindustry, that the institution conduciveness is very much determining the development of the agroindustry itself. The purpose of the study was to formulate strategy of Gayo coffee agroindustry institution by using interpretive structural modeling (ISM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…It means that strategy construction and human resources is an inseparable entity. Studies about close connection between strategy and human resources were also reported by other researchers (Fadhil et al, 2018;Murtadlo and Utomo, 2014;Jaya et al, 2013;).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…It means that strategy construction and human resources is an inseparable entity. Studies about close connection between strategy and human resources were also reported by other researchers (Fadhil et al, 2018;Murtadlo and Utomo, 2014;Jaya et al, 2013;).…”
Section: Resultssupporting
confidence: 53%
“…The ISM concentrates on breaking down complex systems into several simple subsystems and provides a basic understanding of complex situations, and for constructing corrective actions to solve problems. The ISM is widely used in the formulation of operational business strategies (Fadhil et al, 2018).…”
Section: Interpretive Structural Modelmentioning
confidence: 99%
“…One of Indonesia's main arabica coffee producers is in Aceh Province, known as Gayo coffee. Three regencies in Aceh become the main producer central for arabica coffee: Central Aceh, Gayo Lues, and Bener Meriah (Fadhil et al, 2018a). The productivity of arabica coffee in the three regencies reaches 700 to 800 kg ha -1 , and all the coffee fields are cultivated by smallholder plantations (Distanbun Aceh, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is a modeling technique developed for strategic policy planning created by J.Warfield in 1973 as a methodology for structuring relationships between specific items in order to determine the hierarchy of relationships between subject matter and subproblems or complex systems and subproblems. ISM is a simple system and provides a fundamental understanding of the complexity of the problem and formulates a design model to solve problems and formulate business strategies or strategic policies that are operational (Fadhil et al 2018). ISM analyzes system elements and resolves them in graphical form from the direct relationships between elements, idea categories, influence structures, priority structures and hierarchical levels (Attri et al 2013).…”
Section: Methodsmentioning
confidence: 99%